Epicardially placed implantable cardioverter‐defibrillator for a child with congenital long QT syndrome. Issue 3 (10th November 2016) - Sugiyama, Hirotaro; Tachibana, Motomi; Morita, Hiroshi; Nishii, Nobuhiro; Miyoshi, Akihito; Sugiyama, Hiroyasu; Nakagawa, Koji; Watanabe, Atsuyuki; Nakamura, Kazufumi; Ito, Hiroshi
Abstract: A 7‐year‐old boy presented at our hospital with syncope. At birth, electrocardiography had shown a long QT interval with torsade de pointes (TdP). Congenital long QT syndrome (LQTS) had been diagnosed by genetic testing, and was successfully controlled with oral propranolol. At age 7, TdP had recurred with syncope. Electrocardiography revealed a prominent long QT interval with T‐wave alternans. The propranolol dose was increased, but TdP remained uncontrolled. A cardioverter‐defibrillator (ICD) was implanted epicardially, and TdP completely resolved with atrial pacing. We report this rare case of ICD implantation in a child with LQTS.